Pharmaceutical, Pharmacokinetic and Other Considerations for Intravenous to Oral Stepdown Therapy - Peter J Jewesson (Canadian Journal of Infectious Diseases)
Parenteral to oral stepdown therapy represents an effective cost containment strategy which can minimize intravenous therapy associated morbidity and may facilitate earlier hospital discharge. Several oral anti-infectives are available to the prescriber and there are as many opportunities to stepdown to the same agent as there are to other drugs of the same class or other classes. Recognition of the pharmacokinetic characteristics of these oral agents is essential lo successful therapy. Good bioavailability may not always be assured. A simple regimen will promote compliance.